The prognostic value of tumour-infiltrating lymphocytes in pancreatic cancer: a systematic review and meta-analysis. (June 2020) - Orhan, Adile; Vogelsang, Rasmus P.; Andersen, Malene B.; Madsen, Michael T.; Hölmich, Emma R.; Raskov, Hans; Gögenur, Ismail
Abstract: Importance: Tumour-infiltrating lymphocytes (TILs) have previously been found to influence patient prognosis in other gastrointestinal cancers, for instance in colorectal cancer. An immunosuppressive phenotype often characterizes pancreatic cancer with a low degree of immune cell infiltration. Cytotoxic CD8 + T cell infiltration in tumours is found to be the best predictive variable for response to immune checkpoint inhibitor therapy, emphasizing the importance of investigating TILs in pancreatic cancer, especially focussing on CD8 + T cells. Objective: Here, we systematically review the literature and perform meta-analyses to examine the prognostic value of TILs in human pancreatic ductal adenocarcinomas (PDAC). Secondarily, we review the literature regarding the histological localization of TILs and the impact on survival in PDAC. Evidence review: A literature search was conducted on PubMed, Embase, The Cochrane Library and Web of Science. Studies examining patients with PDAC and the impact of high vs. low infiltration of immune cells on long-term oncological survival measures were included. Time-to-event meta-analysis and frequency analysis were conducted using a random effects model. The risk of bias was assessed using the Newcastle-Ottowa Scale. Quality of the cumulative evidence was evaluated using the GRADE approach for prognostic studies. Findings: In total, 1971 articles were screened, of which 43 studies were included in the systematic review and 39 in the meta-analysis. High infiltration of CD8+ lymphocytes was significantly associated with improved overall survival (OS) [hazard ratio (HR) = 0.58, 95% confidence intervals (CIs): 0.50–0.68], disease-free survival (DFS) [HR = 0.64, 95% CI: 0.52–0.78], progression-free survival [HR = 0.66, 95% CI: 0.51–0.86] and cancer-specific survival [HR = 0.56, 95% CI: 0.32–0.99]. A high infiltration of CD3+ T cells was correlated with increased OS [HR = 0.58, 95% CI: 0.50–0.68] and DFS [HR = 0.74, 95% CI: 0.38–1.43]. Infiltration of CD4+ lymphocytes was associated with improved 12-months OS [risk ratio = 0.59, 95% CI: 0.35–0.99] and DFS [risk ratio = 0.68, 95% CI: 0.53–0.88]. High expression of FoxP3+ lymphocytes was associated with poor OS [HR = 1.48, 95% CI: 1.20–1.83]. The greatest impact on survival was observed in the CD8+ T cell and OS group, when infiltration was located to the tumour centre [HR = 0.53, 95% CI: 0.45–0.63]. However, subgroup analysis on the impact of the histological location of infiltration revealed no significant differences between the subgroups (tumour centre, invasive margin, stroma and all locations) in any of the examined cell types and outcomes. Conclusions and relevance: Subsets of TILs, especially CD3 +, CD8 + and FoxP3 + T cells are strongly associated with long-term oncological outcomes in patients with PDAC. To our knowledge, this is the first systematic review and meta-analysis on the prognostic value of TILs in pancreatic cancer. Highlights: High tumour infiltration of T cells in pancreatic cancer predicts better survival. High infiltration of particularly CD8 + T cells corresponds with better outcomes. FoxP3 + T cell infiltration is associated with poor oncological outcomes. T cell infiltration located to the tumour center has the greatest impact on survival. Infiltration of CD20 + lymphocytes and natural killer cells should be further investigated.